Szpitalny system informacyjny (HIS) oparty na metodologii EBM - Walecki, Piotr; Lasoń, Wojciech; Pyrczak, Wiesław; Roterman-Konieczna, Irena; Sarapata, Krzysztof (Hospital Information System (HIS) Based on EBM Methodology, 2006)
The Evidence-Based Medicine (EBM) was described as a new paradigm for clinical decision-making. The EBM paradigm when introduced into Hospital Information System (HIS) enriches a process of diagnosis, and it contributes to the improved quality of recommended decision. This paper presents the EBM methodology for a complex project of clinical data collection and processing, design of workflow, and testing and integration into HIS. Telemedical projects need flexible funding and centralized coordination. Well-designed EBM tool programs will help hospitals working in a computer-based environment to standardize clinical processes (treatment and diagnosis).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1121, s. 168-179